Identifying factors affecting the distribution strategy in the food industry with the attitude of marketing and online sales - solmaz seyedghafouri; Vahid nasehifar; Farid askari (ارزش آفرینی در مدیریت کسب و کار)
Abstract The purpose of this research is to investigate the identification of effective factors on the distribution strategy in the food industry from the point of view of online marketing and sales. This research applicable-developmental is in terms of purpose, qualitative in terms of data collecting method, and a meta-composite approach in terms of the research implementation method. The statistical population of the research includes 12 university professors who are experts in the field of marketing management and distribution channels and have books or articles in this field, as well as theorists and researchers who have specialized studies in this field. This research was analyzed using the scientific method of metasynthesis and by reviewing the published articles; and 85 indicators were extracted based on 23 selected articles. Eventually, 16 components were evaluated and identified, and finally the ultimate framework was confirmed and identified by applying the total opinions of experts on the components of human factors, creating value for the customer, paying attention to the competence of managers, internal factors, external factors, management factors, opinion mining, digital marketing, environmental factors, content marketing, business strategies, complete knowledge of the internal and external environment, direct marketing, visual features, optimization, competitive performance. Extended Abstract Introduction With the growth and expansion of technology, companies have turned to using online methods and channels to sell products and distribute them. The important point is that using online methods is not a substitute for traditional distribution and sales methods; and is used alongside them. In order to apply these methods correctly, strategic marketing planning must be done in businesses, and this has a great impact on pricing and sales (Chen et al, 2021). One of the important issues in production and marketing is how and when to transfer the produced goods to the final consumer. A product may have a good rating in terms of quality, but if it is not offered to the target market at the right time and place, it will lose its usefulness. Therefore, deciding on the way to transfer goods to the place of purchase or consumption is one of the important decisions that the marketing manager faces. These decisions are important in at least two aspects. First, they have a direct effect on other strategic marketing planning decisions, including pricing policy, advertising, packaging, etc., and secondly, the company has to adhere to and remain committed to these decisions for a long time, because the establishment and development of the optimal distribution system takes several years and cannot be changed easily (Barabian & Armon, 2023). Today, due to the multitude and variety of distribution channels, one of the challenges of marketing managers of food industry companies is to choose the right channels, how and how much to use each channel so that the produced goods are offered to the consumer at the lowest cost and at the right time and place (Sharifi & Sharifi, 2022). What is important in the distribution network of goods in a country is the transfer of goods with the least cost and time, along with compliance with the necessary standards to maintain the health of the goods and finally respect the rights of consumers. The goods distribution network in Iran is facing various problems and challenges. The excessive number of trade unions at the traditional retail level, the number of trade unions without business licenses, the prominent share of the unorganized sector compared to the organized distribution and sales network, the lack of benefit from new tools and methods of product distribution, and the lack of interest of the private and foreign sector to invest in modern distribution network are some of the most important challenges of distribution industry in Iran (Thomas, 2017). According to the preliminary review of the literature and the need for a detailed scientific study on how to choose a distribution channel strategy, we can point to this question: how is the identifying of the factors affecting the distribution strategy in the food industry with the attitude of online marketing and sales? Theoretical Framework Distribution channels Distribution channel or marketing channel is the path that goods or services take to reach the ultimate user or consumer. This channel includes all the people who get the ownership of the goods and the people who help to transfer them. The people who are involved in the transfer of ownership of goods, from the producer to the consumer, are called intermediaries. In longer and more complex marketing channels, a class of wholesalers is responsible for larger regions or even countries, buying from manufacturers and selling to smaller wholesalers, sometimes called distributors (Ismailpour, 2017). Online sell Online selling combines the technical and creative aspects of the internet, including design, development, advertising and sales. The emergence of the internet has made it possible for almost everyone to sell their goods, products or services with just a few clicks from buyers. Internet marketing is essentially a continuation of traditional marketing in the past years. Selling through the internet can be beneficial for all small and large businesses. You only need to observe the points that form the core of internet marketing (Mojdkanlou et al, 2022). Riyadi et al, (2023) have conducted a study titled the effect of distribution strategy and price on purchasing decisions from retailers. This study showed that by changing distribution strategies by combining compact, exclusive and selective varieties; significant results were obtained in prices and purchasing decisions by customers. The main finding in this study was that the implementation of distribution strategies to adjust government policies was very effective in reaching customers in all corners of the city so that price adjustments and customer purchase decisions are made continuously. Cao et al, (2023) have conducted a study titled strategic analysis of the influence of distribution strategy on product line design with endogenous quality. By raising the question of whether to emphasize agents or to use wholesalers, the answer to this question depends on the distribution strategy. To solve the problem, a Stackelberg game model with endogenous quality, optimal production and pricing decisions of companies and platforms under different sales models was used. By comparing the equilibrium results, it is clear that both the company and the platform can benefit from product line expansion. When the profit sharing ratio of the platform is in a certain middle range, the company and the platform can agree on the distribution strategy. Also, even if there is no cost to extend the product line, the company will not choose to extend the product line when the platform receives a large portion of the revenue. Research methodology This research applicable-developmental is in terms of purpose, qualitative in terms of data collecting method, and a meta-composite approach in terms of the research implementation method. The statistical population of the research includes 12 university professors who are experts in the field of marketing management and distribution channels and have books or articles in this field, as well as theorists and researchers who have specialized studies in this field. Research findings This research was analyzed using the scientific method of metasynthesis and by reviewing the published articles; and 85 indicators were extracted based on 23 selected articles. Eventually, 16 components were evaluated and identified, and finally the ultimate framework was confirmed and identified by applying the total opinions of experts on the components of human factors, creating value for the customer, paying attention to the competence of managers, internal factors, external factors, management factors, opinion mining, digital marketing, environmental factors, content marketing, business strategies, complete knowledge of the internal and external environment, direct marketing, visual features, optimization, competitive performance. Conclusion The current research was conducted with the aim of identifying factors affecting the distribution strategy in the food industry with the attitude of online marketing and sales. The results of this research are in agreement with the results of Salimi & Hassani (2023), Assarian et al, (2023), Seifbarghy & Kafshian Ahar (2022), Honarmand (2022), Khoi & Jamili (2022), Bashokouh & Beigi Firoozi (2022), Haghighi Kaffash et al, (2021), Riyadi et al, (2023), Cao et al, (2023), Zhang et al, (2023), Sun et al, (2023), Wei & Dong (2022), Salimi & Hassani (2023), Wang et al, (2023), Assarian et al, (2023), and Chen et al, (2021). Seifbarghy & Kafshian Ahar (2022) showed that the integration and coordination of the manufacturer and retailer benefits all members of the supply chain and greatly increases the profit of the entire supply chain. According to the results of the research, the following suggestions are presented: - Examine the features, characteristics and benefits of their product in detail. This analysis includes checking the quality, capabilities, performance, adaptability to customer needs, and competitive advantages of the product. With a detailed understanding of product features and benefits, they can design unique strategies for marketing and selling their product. - They should define their target market precisely and separate its parts. They can pay attention to factors such as gender, age, geographical location, type of industry and other characteristics. By accurately defining the target market, they can design specific strategies for each customer group and improve the sales process.